ATP Content and Cell Viability as Indicators for Cryostress Across the Diversity of Life - Bajerski, Felizitas; Stock, Johanna; Hanf, Benjamin; Darienko, Tatyana; Heine-Dobbernack, Elke; Lorenz, Maike; Naujox, Lisa; Keller, E. R. J.; Schumacher, H. M.; Friedl, Thomas; Eberth, Sonja; Mock, Hans-Peter; et al. (Frontiers in Physiology, 2018)
In many natural environments, organisms get exposed to low temperature and/or to strong temperature shifts. Also, standard preservation protocols for live cells or tissues involve ultradeep freezing in or above liquid nitrogen (-196°C or -150°C, respectively). To which extent these conditions cause cold- or cryostress has rarely been investigated systematically. Using ATP content as an indicator of the physiological state of cells, we found that representatives of bacteria, fungi, algae, plant tissue, as well as plant and human cell lines exhibited similar responses during freezing and thawing. Compared to optimum growth conditions, the cellular ATP content of most model organisms decreased significantly upon treatment with cryoprotectant and cooling to up to -196°C. After thawing and a longer period of regeneration, the initial ATP content was restored or even exceeded the initial ATP levels. To assess the implications of cellular ATP concentration for the physiology of cryostress, cell viability was determined in parallel using independent approaches. A significantly positive correlation of ATP content and viability was detected only in the cryosensitive algae Chlamydomonas reinhardii SAG 11-32b and Chlorella variabilis NC64A, and in plant cell lines of Solanum tuberosum. When comparing mesophilic with psychrophilic bacteria of the same genera, and cryosensitive with cryotolerant algae, ATP levels of actively growing cells were generally higher in the psychrophilic and cryotolerant representatives. During exposure to ultralow temperatures, however, psychrophilic and cryotolerant species showed a decline in ATP content similar to their mesophilic or cryosensitive counterparts. Nevertheless, psychrophilic and cryotolerant species attained better culturability after freezing. Cellular ATP concentrations and viability measurements thus monitor different features of live cells during their exposure to ultralow temperatures and cryostress.